Sugar-linked biodegradable polymers: regio-specific ester bonds of glucose hydroxyls in their reaction with maleic anhydride functionalized polystyrene and elucidation of the polymer structures formed - Galgali, P.; Agashe, M.; Varma, Anjanikumar (Carbohydrate Polymers, 2007)
In the development of sugar-linked synthetic polymers as biodegradable polymers, it is imperative to know the variety of polymer structures formed by the reaction of a multi-functional sugar molecule with the functionalized synthetic polymer on which the sugar is to be anchored. Enzymes produced by the microorganisms causing the polymer to biodegrade can be sensitive to the particular type of sugar hydroxyl utilized (such as anomeric, primary, or secondary hydroxyl group) for getting anchored to the polymer. In this paper, we present synthesis of regio-specific ester derivatives of glucose with anhydride, functionalized polymers, i.e., ester formation specifically with the anomeric, primary or secondary hydroxyls of glucose. Characterization of these different esters groups was done using FTIR spectroscopy; each ester peak was further deconvoluted to yield its different components. For this purpose, we studied the reactions of D-glucose, 6-O-trityl glucose, methyl glucoside, 1,2-5,6-diisopropylidene-D-glucose, and 1,2,3,4-tetraacetyl-D-glucose with maleic anhydride functionalized polystyrene (PSMAH). In this study, the primary hydroxyl of glucose was found to be even more reactive than the anomeric hydroxyl. The peaks at similar to 1716, similar to 1725, and 1729-1737 cm(-1) were assigned to the ester carbonyl of the anomeric, primary, and secondary hydroxyls of glucose (C2, C3, and C4), respectively. An attempt was made to quantify the extent to which the different polymer structures are formed in a particular reaction by taking ratios of non-variable reference peaks (polystyrene peak at 1493 cm-1) and variable peaks caused by the reaction (the residual anhydride carbonyl at 1780 cm(-1)). (c) 2007 Published by Elsevier Ltd.
Keywords: Biodegradable polymers; functionalized synthetic polymer; glucose; regio-specific; sugar-linked polystyrene